Taxonomic status of the narrow endemic Astragalus robbinsii var fernaldii (Fernald's Milkvetch - Fabaceae): molecules, morphology, and implications for conservation - Sokoloff, Paul C (University of Ottawa (Canada), 2010)
Astragalus robbinsii var. fernaldii (Fernald's Milkvetch) is a federally listed taxon of "special concern" due for re-assessment by COSEWIC. Restricted to the Strait of Belle Isle region of Atlantic Canada, its taxonomy in respect to two co-occurring congeners, Astragalus eucosmus and Astragalus robbinsii var. minor, has been questioned due to the variable states of the varieties' diagnostic characters. To clarify phylogenetic relationships within this species complex we studied variation in chloroplast DNA, AFLPs and morphology. Chloroplast DNA sequence data distinguished A. r. var. minor from A. eucosmus and most A. r. var. fernaldii. Three A. r. var. fernaldii populations possessed the A. r. var. minor haplotype, and AFLPs revealed no population structure, indicative of gene flow between taxa and populations. Morphometric analysis indicates that A. r. var. fernaldii is closer to A. eucosmus than A. r. var. minor. Based on these results taxonomic recognition of A. r. var. fernaldii is unwarranted, and we recommend that the taxon be merged into A. eucosmus.
Keywords: Biology, Systematic.